Cry in the night [large type] - Hart, Carolyn G. (Thorndike Press large print mystery series., 2014)
"Egyptologist Sheila Ramsay develops a newfound interest in MesoAmerican affairs after meeting an outspoken--and attractive--Mexico City curator, a harsh critic of museums that deal in stolen art. And her own museum gives her the perfect opportunity to see him again: a valuable Aztec manuscript needs to be returned to its rightful owners, the wealthy Ortega family. But things don't go as planned for Sheila south of the border. An anonymous note threatens her with death if she remains in Mexico City. The curator she longed to see treats her with contempt. And the Ortegas are as mysterious as they are charming. What Sheila has stumbled into is much bigger--and more deadly--than she ever dreamed. And amid the splendor of Mexico's ancient ruins and treacherous hillsides, Sheila will realize that there's no one she can trust..."-- Page [4] of cover.